Penanaman Modal Asing di Indonesia Dan Hambatannya - Marcel Seran (Jurnal Pemberdayaan Hukum, 2011)
Improving economic growth of a country needs quite a big amount of fund. Funding of the country as expected as source of money is not enough, so alternative choice of fund neded is through direct foreign investment. But this is not an easy way. A lot of problem faced, for instance, the inadequate infrastructures, the dificulty in procedure of getting permit, instability of political situation, unrealibility of law to support and to protect which are usually block foreign investor. And also those problems cause the foreign investor remove their investment to another country. Because of that, is needs a dealing to the problems so that the foreign investor interest to invest in Indonesia.